Land Use Planning Made Plain - Leung, Hok-Lin (Heritage, 2020)
Land Use Planning Made Plain is a practical guide for planners, administrators, politicians, developers, property owners, and the general public on how to make and implement land use decisions. It seeks to develop a set of coherent planning principles by drawing out useful and generally applicable elements from various systems and approaches.Hok-Lin Leung's focus is on planning at the city level, and he has organized the text according to the logical sequence of plan-making: justifications for making a land use plan, a plan for plan-making, planning goals, information, analysis, synthesis, and implementation. He addresses major debates in land planning today, including controversial material, and concludes with suggestions on the qualifications and qualities of a land use planner. By encouraging a shared understanding of the purpose, analytic skills and substantive considerations of plan-making – as well as the ways and means of plan-implementation – this book helps the planner to become more responsible and responsive to the many issues surrounding land use and its important role in addressing human needs